2021
DOI: 10.1007/s10047-021-01264-6
|View full text |Cite
|
Sign up to set email alerts
|

Rescue extracorporeal membrane oxygenation for massive anterior mediastinal masses

Abstract: The management of massive anterior mediastinal masses (AMM) is challenging. With the burgeoning role of extracorporeal membrane oxygenation support (ECMO) beyond the confines of salvage therapy, more trained clinicians are adopting it as a bridge for high-risk procedures or situations where temporary respiratory or cardiac support is required. We report our experience with using ECMO in the management of massive AMM in this case series of three patients sharing their clinical details and the lessons learned fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Timely transferal to a tertiary referral center with experience in cardiothoracic surgery and mechanical circulatory support is key in preventing catastrophic cardiorespiratory decompensation. Our case also demonstrated that ECMO can be successfully used in pediatric patients with massive mediastinal mass as a cardiovascular support modality during surgical treatment, for which there is only a limited number of pediatric case reports (26,27). Multi-disciplinary input is essential to facilitate tumor resection and to minimize morbidity and mortality.…”
Section: Discussionmentioning
confidence: 77%
“…Timely transferal to a tertiary referral center with experience in cardiothoracic surgery and mechanical circulatory support is key in preventing catastrophic cardiorespiratory decompensation. Our case also demonstrated that ECMO can be successfully used in pediatric patients with massive mediastinal mass as a cardiovascular support modality during surgical treatment, for which there is only a limited number of pediatric case reports (26,27). Multi-disciplinary input is essential to facilitate tumor resection and to minimize morbidity and mortality.…”
Section: Discussionmentioning
confidence: 77%
“…Table 1 summarizes the cases of ECMO in patients with hematological malignancies of the anterior mediastinal [5][6][7][8][9][10][11][12][13][14][15], including the present case, focusing on the intensive care period, airway management, and complications. The stenosis site extended from the lower part of the trachea to the bifurcation or the main bronchus in all cases, suggesting that ECMO introduction might be needed when respiratory management is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…An ECMO might be useful as a bridge to chemotherapy in patients with airway emergencies to increase the survival rate for such patients [ 4 ]; however, remission-induction chemotherapy causes neutropenia and an immunocompromised state, placing patients at risk of severe infections, such as ventilator-associated pneumonia. In such situations, ES may shorten the intensive care period [ 5 ]. Hence, planned ECMO and ES can be appropriate for respiratory management of these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical conditions and anaesthesia can exacerbate this, further reducing cardiac output. Both VV and VA-ECMO have been utilised to provide perioperative support during resection of large mediastinal tumours (57). VA-ECMO may be preferred due to the additional haemodynamic support it offers.…”
Section: Mediastinal Pathologymentioning
confidence: 99%